Rastros de uma voz : a instância gráfica na cinescrita de Agnés Varda - Ronna, Giulianna Nogueira (2019)
In this work, I search to reflect on the graphic instance in Varda’s cinécriture, as a resource that reveals tracks of a voice. I approach the concepts of vestige, track and trace in Benjamin (2006) and Derrida (2001) to aspects of narration and filmic figure in Dubois (2005), enabling a reflection centred in ways of inscription in the movie that are able to modify the visible and readable components of the image. For this, I analyse the graphic instance in the films Happiness (Le Bonheur, 1965), Vagabond (Sant toit ni loi, 1985) and The beaches of Agnès (Les plages d’Agnès, 2008). These analyses expound how narration, built from this instance, suggest what is no longer visible, but remains latent in visuality. This way, the graphic participates of a visibility mode that organizes itself in the track experience, stating something about the film.